Green synthesis of nanoparticles for the remediation of contaminated waters and soils: Constituents, synthesizing methods, and influencing factors. (20th July 2019) - Wang, Yinan; O'Connor, David; Shen, Zhengtao; Lo, Irene M.C.; Tsang, Daniel C.W.; Pehkonen, Simo; Pu, Shengyan; Hou, Deyi
Abstract: Diverse types of engineered nanoparticles (NPs) have been developed, including products used for the remediation of contaminated waters and soils. However, conventional NP production, whether by physical or chemical assembly, is associated with secondary impacts to human health and the environment. Green synthesis is an emerging field dedicated to the development and improvement of NP production in an effective, non-hazardous, and eco-friendly manner. This can be achieved by either: (i) the use of green materials as synthesis reagents, or (ii) employing production methods that consume less energy or natural resources. Numerous efforts have been expended to find greener materials or methods for these purposes. For instance, natural plant extracts and microbiological materials have been investigated as reducing, capping, and stabilizing reagents, and microwave energy has been explored as a way to reduce energy and reagent requirements. Green synthesis researchers are increasingly developing new NPs to treat a wide range of environmental contaminants, including heavy metals and organic pollutants. For instance, nano-scale zero valent iron synthesized with green tea extract has been reported to be effective at reducing soil bound Cr(VI) concentrations. Among the main challenges for the synthesis of NP products for environmental remediation is the ability to control the particle size and morphology. It was found that variables in green synthesis processes, such as pH, temperature, reaction/incubation time, and the use of different stabilizers can directly influence such characteristics. This review provides an overview of the various green synthesis constituents and methods that have been developed to date, characterizes green NPs including their sizes and morphologies, and considers their performance in the remediation of contaminated soils and waters. Recommended future directions are put forward to fill in the research gaps.